Bullying and psychosocial adjustment among children with and without asthma. Issue 1 (5th June 2021) - Runions, Kevin C.; Cross, Donna S.; Vithiatharan, Rena; Everard, Mark; Hall, Graham
Abstract: Children with asthma face serious mental health risk, but the pathways remain unclear. This study aimed to examine bullying victimisation and perpetration in children with asthma and a comparison sample without a chronic health condition, and the role of bullying in moderating psychosocial adjustment outcomes for those with asthma. A sample of children with ( n = 24) and without asthma ( n = 39), and their parents, were recruited from hospital clinics. Parents rated children's psychosocial adjustment; children provided self-report of bullying victimisation and perpetration; from which co-occurring bully/victim status was derived. No differences in mean perpetration or victimisation were found, but children with asthma were more likely to be bully/victims (involved both as target and perpetrator), compared to those without asthma. Children with asthma who were victims of bullying had greater peer problems and overall adjustment problems; bully/victims did not show this pattern. Children with asthma may be more likely to be bully/victims, and those who are victims of bullying may be at elevated risk for psychosocial adjustment problems and require particular support in this area from school counsellors and psychologists.